Conceptual model of the Gülbahçe geothermal system, Western Anatolia, Turkey: Based on structural and hydrogeochemical data. (July 2017) - Uzelli, Taygun; Baba, Alper; Gül Mungan, Gamze; Dirik, R. Kadir; Sözbilir, Hasan
Highlights: Tectonic is one of the important parameters for geothermal system. Most of the geothermal systems in western Anatolia are controlled by normal faults. Geothermal system of the Gülbahçe is controlled by a strike-slip dominated shear zone. Negative flower structure is primary control mechanism for the geothermal system. Gulbahce geothermal fluids are formed by local recharge and deep circulation of sea water. Abstract: The Gülbahçe Geothermal Field is located on the eastern margin of the Karaburun Peninsula, about 45 km from the city of İzmir, western Anatolia, Turkey. The stratigraphy of the study area is represented by a Miocene volcano-sedimentary succession, including several sedimentary and volcanic units. These units overlie the basement rocks of the Karaburun Platform and Bornova Flysch Zone which consist of sandstones, shales and carbonate blocks. These rock units are cut and deformed by a series of NW-SE- to NE-SW-trending faults, extending from Sığacık Bay to Gülbahçe Bay. Structural studies suggest that while most of the geothermal systems in western Anatolia are controlled by normal faults, the geothermal system at Gülbahçe is controlled by a strike-slip dominated shear zone, previously named the İzmir-Balıkesir Transfer Zone. Along the fault zone, associations of active fault segments accommodate deep circulation of hydrothermally modified sea water, and thus the resulting negative flower structure is the primary control mechanism for the geothermal system. Hydrogeochemical properties of the field show that surface temperature of fluid ranges from 30 to 34 °C. Geothermal fluids in Gülbahçe have high salinity (EC > 34 mS/cm) and low enthalpy. Piper and Schoeller diagrams indicate that geothermal fluid is in the NaCl facies. Chemical geothermometers suggest that the reservoir temperature is around 53–136 °C. The isotopic data (oxygen-18, deuterium and tritium) suggest that geothermal fluids are formed by local recharge and deep circulation of sea water.